Covid-19 Pandemic and Exit Policy Strategy: A Cluster Analysis using R - As-Salafiyah, Aisyah; Riani, Ririn; Soeparno, Wahyu Sugeng Imam (SMART Insight, 2023)
This bibliometric research investigates trends from various studies on exit policy strategies through economic policies in multiple countries during the COVID-19 pandemic in the scientific literature published by the Scopus-indexed journal. The data analyzed were 740 research publications discussing exit policy during the COVID-19 period. The search determined research datasets in the publishing range from 2019 to 2021. The data is then analyzed using the R application program to determine the bibliometric mapping of exit policy research developments during the COVID-19 pandemic. The results show that in the visualization of the mapping of research developments on this theme, the keywords that appear the most are Fiscal Policy, Macroeconomics, Monetary Policy, Economic Recovery and Gross Domestic Product. Based on the cluster analysis, it can be concluded that there are at least four research lines, namely: (1) exit policy on fiscal; (2) exit policy and public health; (3) exit policy on monetary policy; and (4) exit policy and SMEs. This study also provides information about exit policies on economic policies implemented in various countries in the face of the COVID-19 pandemic.